2008
DOI: 10.4142/jvs.2008.9.3.257
|View full text |Cite
|
Sign up to set email alerts
|

Plasma haptoglobin and immunoglobulins as diagnostic indicators of deoxynivalenol intoxication

Abstract: This study aimed to discover potential biomarkers for dioxynivalenol (DON) intoxication. B6C3F1 male mice were orally exposed to 0.83, 2.5 and 7.5 mg/kg body weight (bw) DON for 8 days and the differential protein expressions in their blood plasma were determined by SELDI - Time-of-Flight/Mass Spectrometry (TOF/MS) and the immunoglobulins (Igs) G, A, M and E in the serum were investigated. 11.7 kDa protein was significantly highly expressed according to DON administration and this protein was purified by emplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 34 publications
2
6
0
Order By: Relevance
“…In the studies with horses (Raymond et al 2003(Raymond et al , 2005, no DON-induced changes in serum haptoglobin were described, but this might result from the lower dosages used (3 and 5 mg DON/100 kg BW, respectively). The elevation of serum haptoglobin observed in the present study in conjunction with reduced IgA levels was also shown in mice (Kim et al 2008). Mice receiving daily 2.5 and 7.5 mg DON/kg BW, showed a 1.5-and 2.9-fold increase in serum haptoglobin levels.…”
Section: Archives Of Animal Nutrition 155supporting
confidence: 74%
“…In the studies with horses (Raymond et al 2003(Raymond et al , 2005, no DON-induced changes in serum haptoglobin were described, but this might result from the lower dosages used (3 and 5 mg DON/100 kg BW, respectively). The elevation of serum haptoglobin observed in the present study in conjunction with reduced IgA levels was also shown in mice (Kim et al 2008). Mice receiving daily 2.5 and 7.5 mg DON/kg BW, showed a 1.5-and 2.9-fold increase in serum haptoglobin levels.…”
Section: Archives Of Animal Nutrition 155supporting
confidence: 74%
“…Recent reports highlight the value of urinary DON as a biomarker of recent exposure [12][13][14] while immunoglobulins and pro-inflammatory cytokines have been proposed as potential biomarkers of effect in relation to the immunomodulatory effects of the compound [8,15].…”
Section: Introductionmentioning
confidence: 99%
“…Despite these observations the etiology of many outbreaks remains unknown. Biomarkers promise to provide more objective measures of DON exposure in order to explore disease associations, but few such studies have been conducted although exposure of DON affects immune cells immunoglobulins and pro‐inflammatory cytokines 10–12. The identification of biomarkers of exposure has focused on the urinary levels of the parent compound and its glucuronide conjugate 13, 14.…”
Section: Introductionmentioning
confidence: 99%